PEMBAGIAN HARTA BERSAMA SETELAH PERCERAIAN DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU (Studi Kasus Terhadap Putusan Pengadilan Agama Rengat Nomor : 062/Pdt.G/2009/PA Rengat) - Fendra Yuli Hardiyanto; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Joint property is marital property acquired during marriage by both husband and wife, who are in the power of the husband and wife together, so that use should be made with the consent of both parties (unless provided otherwise in the marriage covenant). Joint property is set in the Compilation of Islamic Law Article 97 which states: